The cGAS-STING pathway in viral infections: a promising link between inflammation, oxidative stress and autophagy - Zhang, Kunli; Huang, Qiuyan; Li, Xinming; Zhao, Ziqiao; Hong, Chun; Sun, Zeyi; Deng, Bo; Li, Chunling; Zhang, Jianfeng; Wang, Sutian (Frontiers in Immunology, 2024)
The host defence responses play vital roles in viral infection and are regulated by complex interactive networks. The host immune system recognizes viral pathogens through the interaction of pattern-recognition receptors (PRRs) with pathogen-associated molecular patterns (PAMPs). As a PRR mainly in the cytoplasm, cyclic GMP-AMP synthase (cGAS) senses and binds virus DNA and subsequently activates stimulator of interferon genes (STING) to trigger a series of intracellular signalling cascades to defend against invading pathogenic microorganisms. Integrated omic and functional analyses identify the cGAS-STING pathway regulating various host cellular responses and controlling viral infections. Aside from its most common function in regulating inflammation and type I interferon, a growing body of evidence suggests that the cGAS-STING signalling axis is closely associated with a series of cellular responses, such as oxidative stress, autophagy, and endoplasmic reticulum stress, which have major impacts on physiological homeostasis. Interestingly, these host cellular responses play dual roles in the regulation of the cGAS-STING signalling axis and the clearance of viruses. Here, we outline recent insights into cGAS-STING in regulating type I interferon, inflammation, oxidative stress, autophagy and endoplasmic reticulum stress and discuss their interactions with viral infections. A detailed understanding of the cGAS-STING-mediated potential antiviral effects contributes to revealing the pathogenesis of certain viruses and sheds light on effective solutions for antiviral therapy.